Dangerous boys and their toy eaudiobook - Black, Shayla (Tantor Media, 2018)
Trading orgasms for information isn't their usual way of doing business, but when a missing criminal-turned-star-witness and fifty grand are on the line, bounty hunter R. A. Thorn and Detective Cameron Martinez are prepared to put their bodies to the task and give gorgeous Brenna Sheridan everything she needs. An exchange they never anticipated becomes an experience none can forget—or walk away from. Sexual hunger sizzles the threesome, but the stakes and danger rise as a mafia bad-ass stalks Brenna. Soon, their "deal" is no longer about information—or sex. Emotions bind Brenna, Cam and Thorn together more tightly than they ever imagined as the men protect—and serve—the beloved woman neither can live without. Contains mature themes.